SEGMENTASI KONSUMEN BERDASARKAN FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM MEMILIH KAFE - Muhammad Ikhsan Sulaiman; Risnadi Irawan; Yusriana Yusriana (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
Increasing economic growth and number of middle-class consumers has encouraged growing number of modern cafés in the middle-income countries in South East Asia and China. The modern café is marked by serving Arabica coffee, the existence of barista, the use of espresso machine and knowledge of coffee culture. Café owners need to know their customers for developing business strategy. This study is aimed to classify the customers into different segment based on the factors influencing customer decision in choosing the place for drinking coffee. Ten cafés were purposive sampled and a hundred of customers were randomly selected and requested to fill a questioner. Principle component analysis were used to extract the customer attributes into 6 segments. Rotation of loading factors has helped this research to characterize each segment into conventional, sociality, trendy, coffee lover, lifestyle and healthy type of customer and at the same time to get know the size of each segment.